Marsilii de Inghen Quaestiones super quattuor libros "Sententiarum" : Super tertium, quaestiones 1-5 - Wojtczak, Hanna (Early Modern History and Modern History E-Books Online, Collection 2023., 2023)
This edition contains quaestiones 1-5 of book III of the commentary on the Sentences, by Marsilius of Inghen (†1396), the founding rector and first doctor of theology of the University of Heidelberg. These questions are devoted to the Christology, Mariology, and Trinitology, and deal with the issue of the Incarnation of Christ, with quaestiones 1-3 considering it in relation to the individual Persons of the Trinity, and quaestiones 4-5 in relation to the Blessed Virgin Mary. In all questions, Marsilius advocates the via media of sound faith, even above any school traditions.